Turkey between nationalism and globalization - Kastoryano, Riva (London : Routledge, Taylor & Francis Group, 2013)
'Turkish society has been going through institutional and ideological change that has affected its social, cultural and political practices. This book examines these contemporary tensions, which have led to a re-appraisal of Turkey as a nation and Turkish nationalism as it tries to situate itself as a regional and global power'--
Includes bibliographical references (pages 214-216) and index.
Keywords: Nationalism -- Turkey; Turkey -- Foreign relations -- 1980-; Turkey -- Politics and government -- 1980-